Studi Literatur : Luaran Fungsional Pasien Hirshcsprung Pasca Pull-Through Berdasarkan Skor Rintala - Muhammad Arvienji Wardaya; Miftahurrahmah Miftahurrahmah; Esa Indah Ayudia; Willy Hardy Marpaung; Humaryanto Humaryanto; Budi Justitia (Litbang PWM Jawa Tengah, 2022)
Hirschsprung's disease is a disorder that causes interference with the absence of innervation in the colon, causing peristalsis in the colon. Treatment of Hirschsprung performed surgically using the Pull-through method. Data regarding the post-pull-through functional outcome has not been obtained, especially in Indonesia. Using the Rintala score, this study aims to analyze the functional outcome of post-pull-through Hirschsprung patients based on the Rintala score from a literature study. This study used a literature review approach as many as fifteen literature sources from Google Scholar, Pubmed, Science Direct, Elsevier and DOAJ according to the inclusion criteria set by the researcher. Based on the results of the literature study, from 15 literatures there are 14 literature have information about the age, sex, and complications of Hirshscprung patients after the pull-through. And from 15 literatures, all literature has information about post Pull-though evaluation using the Rintala score and the type of Pull-through operation used. Based on the gender of the Hirschsprung patient, it was more common in boys, the age at evaluation ranged from 3 to 11 years. Post pull-through complications are enterocolitis, anastomotic stricture, and constipation. The results of the Rintala scoring show that the interpretation of